1994
DOI: 10.1093/oxfordjournals.eurheartj.a060654
|View full text |Cite
|
Sign up to set email alerts
|

Survival after coronary artery bypass grafting Experience from 4661 patients

Abstract: The duration of the reduction of mortality after coronary artery bypass grafting (CABG) is an important issue and this study was undertaken to evaluate time in relation to excess mortality among CABG patients compared with the general population. Survival was analysed in 4661 patients who had undergone their first isolated CABG. Observed survival was related to that expected among subjects from the general Swedish population stratified by age, sex and 5-year calendar period, to calculate relative survival and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
1
7
0
3
Order By: Relevance
“…In accordance with previous studies, higher age was as an independent predictor of observed long-term mortality, and relative survival analyses revealed that the effect of age was attributable to the population risk [ 13 , 14 , 16 ]. On the contrary, relative mortality increased with decreasing age, also after adjustment for smoking and comorbidities.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous studies, higher age was as an independent predictor of observed long-term mortality, and relative survival analyses revealed that the effect of age was attributable to the population risk [ 13 , 14 , 16 ]. On the contrary, relative mortality increased with decreasing age, also after adjustment for smoking and comorbidities.…”
Section: Discussionsupporting
confidence: 91%
“…Ståhle et al [8] reported worsening survival eight years after CABG compared with the general population. In our study, the Kaplan-Meier curves describing the risk of death or a new CHD event also showed that the results of the CABG began to deteriorate about ten years after the CABG.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies evaluating the long-term outcome of CABG operations are from a single specialised centre [5][6][7][8][9][10][11] or studies comparing different operation techniques [12][13][14]. Even though several studies have evaluated the long-term survival of CABG patients compared with the survival of the background population at the national level [5,[7][8][9][10][15][16][17] there are very few data on the longterm survival after CABG compared with the background population of the exact same geographical area from which the CABG subjects are taken. Furthermore, few studies have separately analysed all-cause mortality, coronary heart disease (CHD) mortality and non-fatal CHD events in both male and female patients.…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up studies indicate that the survival after CABG is similar to that in the population at large over the first 7–8 years [7] or even longer [8]. However, in a very long-term perspective, the mortality from coronary artery disease might increase as the surgical effect diminishes.…”
Section: Introductionmentioning
confidence: 99%